Komposisi Bakteri Saluran Pencernaan Belut Rawa (Synbranchus Bengalensis) - Arista Suci Andini; Faturrahman Faturrahman; Wahyu Hurriatul Khair (Fakultas MIPA UNM, 2021)
Abstract. Eels are a group of snake- shaped fish belonging to the Synbranchidae. Bacteria in groups of fish such as eels can be found on the body surface and digestive tract. Some bacteria are pathogenic, while a number of other bacteria are beneficial, but researches in this topic has not been optimal. This study examined the bacterial composition of the digestive tract of swamp eel (Synbranchus bengalensis) using descriptive exploratory methods. The results showed that the composition of bacteria found in the digestive tract of swamp eels was diverse but dominated by gram-positive bacteria; BR2, BR3, BR4, BR5. In addition, some of these bacteria belong to the group of proteolytic bacteria; BR2 and BR4, lipolytic bacteria; BR2, and amylolytic bacteria; BR1 which hydrolyzes digestive enzymes can act as probiotics in the digestive tract of swamp eels (Synbranchus bengalensis).Keywords: swamp eels, microflora digestive, Synbranchus bengalensis